Fault classification in inverter based resources system using spherical coordinate system - Vivek Sahu; Pratim Kundu (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2025)
Modern grid codes require renewable energy source (RES) plants to remain connected with the grid even during fault scenarios. Fault current being comparable to rated full-load output of RES plants, makes timely fault analysis a more challenging task. In this work, fault detection and classification on a network based fully on inverter-based resources (IBRs) is proposed. Discrete Fourier transformation is utilized to extract fundamental component of three-phase voltages and currents. Two separate indices for fault classification, based on Spherical Coordinate System (SCS)-based representation is proposed. Mathematical derivations form the underlying basis for simplistic threshold settings. Based on the indices, decision variables are set. Sign-based identification of faulty phase(s), without the need of prior fault-type identification, is done by a new category of power variables. Final decision is reached through a proposed trip logic. Timely response of fault analysis is identified to be within practical limits to suit industrial requirements. The methodology is tested on a modified IEEE 9-bus model using PSCAD/EMTDC. Different fault types, fault distance, inception angle and resistance are found to validate the threshold settings. Satisfactory performance during switching events like load, generator and line tripping ensures its robustness.